Differential Rod Contouring is Essential for Improving Vertebral Rotation in Patients With Adolescent Idiopathic Scoliosis: Thoracic Curves Assessed With Intraoperative CT. Issue 10 (15th May 2018) - Seki, Shoji; Newton, Peter O.; Yahara, Yasuhito; Makino, Hiroto; Nakano, Masato; Hirano, Norikazu; Kawaguchi, Yoshiharu; Kimura, Tomoatsu
Abstract : Study Design: A case series. Objective: We investigated the contributions of rod contouring and differential rod contouring (DRC) to the reduction of apical axial vertebral body rotation in patients with adolescent idiopathic scoliosis (AIS). Summary of Background Data: DRC is used for posterior spinal correction and fusion. The contribution of DRC to vertebral body derotation is unclear. Methods: We analyzed the results of intraoperative computed tomography (CT) in 40 consecutive AIS patients with thoracic curves (Lenke type I or II, 35; type III or IV, 5). Rod contour before initial rod rotation was analyzed by x-ray. Periapical rod contour between concave and convex rod rotation (RR) were analyzed by cone-beam CT imaging. To analyze the reduction of vertebral body rotation with DRC, intraoperative cone-beam CT scans of the three apical vertebrae of the major curve of the scoliosis (120 vertebrae) were taken post-concave RR and post-convex DRC in all patients. The angle of vertebral body rotation was measured. In addition, the contribution of rod contouring to apical vertebral body derotation was analyzed. Rib hump indices (RHi) were measured by pre- and postoperative CT. Results: The mean vertebral body rotation angles post-concave RR and post-convex DRC were 15.3° and 9.3°, respectively, for a mean reduction of vertebral rotation in convex DRC after concave RR of 6.0° for thoracic curves ( P < 0.001). The RHi was significantly improved by DRC ( P < 0.05). Improved apical vertebral rotation was significantly correlated with the difference of apical rod curvature between concave and convex. Vertebral derotation was significantly higher in curves with > 10° difference between concave and convex rod curvature than differences < 10°. Conclusion: DRC contributed substantially to axial derotation and reducing rib hump in thoracic scoliosis. The degree of apical rod curvature correlated with the degree of apical vertebral derotation. Level of Evidence: 4